VIRTUAL ACCOUNT SANTRI : IKHTIYAR PESANTREN DALAM MEMBERIKAN LAYANAN PRIMA BERORIENTASI CUSTOMER SATISFACTION DI PONDOK PESANTREN - Hasan Baharun; Rizaqil Ardillah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri (UIN), 2019)
This article presents the services which is provided by Nurul Jadid Islamic Boarding School using the Virtual Account payment method. In essence, the purpose of a service is to provide a sense of satisfaction for the people who is being served. To achieve this level of satisfaction must be accompanied by facilities and personnel from each side. In providing a service we are required to be sensitive to the wishes and needs of customers. Through the Virtual Account method can be implemented in financial management, especially in the payment process in an educational institution because it can provide convenience, and can be guaranteed in the process of payment transactions. By using this method, the Islamic Boarding School's treasurer can provide services in the form of convenience, guarantees, and concerns of Islamic Students (Santri) or Islamic Student's Parent (Walisantri) when processing payment transactions.